Adaptive Control Strategy for Power Flow Controller With Disturbance Mitigation Using Discrete Wavelet Transform in Renewable Energy Source Integrated Railway Systems - Hamed Jafari Kaleybar; Morris Brenna; Mariacristina Roscia (IEEE Access)
The growing direct integration of renewable energy sources (RES) into railway power networks has increased their vulnerability to power quality (PQ) disturbances and dynamic variations. To address these challenges, a novel control strategy for the railway power flow controller (RPFC) to increase its capacity for compensation and dynamic performance is presented. An adaptive discrete wavelet transform-based control scheme, incorporated into a twofold instantaneous reactive power method (ADW-TIRP) is proposed to enhance RPFC performance under fluctuating operating conditions. The proposed adaptive method is designed to operate effectively with various traction substation transformer configurations, including the main ones V/V and Scott transformers. The key advantages of the ADW-TIRP approach lie in its superior suppression of a wide spectrum of harmonic components, its robust dynamic response against time-varying train loads, and its enhanced robustness against disturbances caused by the integration of RESs into the railway network. The suggested control strategy’s efficacy is demonstrated through MATLAB/SIMPOWER simulations for different scenarios, validating its capability to improve PQ and system stability under different disturbances situations. Simulation results show that the proposed ADW-TIRP method consistently maintains low THD, significantly reduces negative-sequence currents, and outperforms conventional methods such as TLPF and VFR-based strategies in transient immunity, harmonic suppression, and current balancing, confirming its suitability for modern, large-scale electrified railway systems.